Evaluation of prescription pattern in terms of essentiality and rationality and assessment of Hospital pharmacy services utilization in tertiary care teaching rural hospital. - AM, Shah; JV, Dhanani; RB, Shah; A, Agrawal; BM, Gajjar (Indian Journal of Pharmacy Practice)
To evaluate the prescription pattern in terms of essentiality and rationality and assessment of Hospital pharmacy services utilization in tertiary care teaching rural hospital. A Prospective Observational Study was conducted. Total 100 patients attending various outpatient departments of Shree Krishna Hospital, a tertiary care teaching hospital were interviewed at their exit from the hospital and necessary information was gathered. Average time taken for interview with patient was 8.3 minutes with range of 7 to 10 minutes. All the prescriptions collected were analyzed for different parameters. Total 350 drugs were prescribed and average number of drugs per prescription was 3.5. Out of these 350 drugs, 60 (17.14%) were prescribed by generic name and the rest 290 (82.86%) were prescribed by brand name. Only 18 (5.14%) drugs were not prescribed from hospital formulary. 264 (75.43%) drugs were dispensed from the hospital pharmacy. On the basis of rationality score 53% prescriptions were rational, 30% semi rational and 17% irrational. Average rationality score was 20.56. In a hospital, where hospital formulary is based on WHO Essential medicine list, hundred percent utilization of hospital pharmacy services by doctors and patients would ensure rational prescribing for the benefit of the patients
Keywords: prescription; out-patient; WHO; formulary